Analysing citizens' perceptions of renewable energies in rural areas: A case study on wind farms in Spain. (November 2022) - Duarte, Rosa; García-Riazuelo, Álvaro; Sáez, Luis Antonio; Sarasa, Cristina
Abstract: The promotion of rural development can benefit from the advancement of renewable energies as potential sources of growth and income in an integrated economy. Rural areas have attracted a significant proportion of renewable energy installations, mainly wind energy. Moreover, the development of renewables has been explicitly claimed as a key instrument to support rural economies through job creation, new sources of income for landowners and local authorities, and more sustainable industries with the revitalization of their productive systems. However, the installation of renewable energies can have, in the short and long term, different impacts on the territory. This study explores Campo de Belchite citizens' perception of the effects wind energy installations has on the economy, demography, and employment opportunities. The Campo de Belchite county (Aragon) was used as a case study due to its wind-farm development. Citizens perceptions on the socio-economic effects and expectations of renewable energies have been explored on the basis of their responses to an online survey. Findings show a great heterogeneity between agents and territories, both in the evaluation of impacts and in their hopes. The management model plays a critical role for achieving its social acceptance. This work contributes with industrial and energy policy insights that call for a more decentralized, participatory and transparent management models. Highlights: The perception of the socio-economic impacts of wind energy in rural areas is assessed. A survey-based approach was conducted. Heterogeneity of results is found between hopes and reality. Social acceptance is key to the development of renewable energies.